A Review of Metaverse and Cybersecurity in the Digital Era - Jaipong, Parichat; Siripipattanakul, Sutithep; Sriboonruang, Patcharavadee; Sitthipon, Tamonwan (International Journal of Computing Sciences Research; Vol 7 (2023): Volume 7, 2023)
Purpose – Adoption of the metaverse may increase cybersecurity risks. This study evaluates the literature on metaverse and cybersecurity in the digital era. Method – A narrative synthesis was used in this review article. The literature and information were reviewed systematically to explore metaverse and cybersecurity in the digital era from various books and research articles on EBSCO, Google Scholar, Scopus, Web of Science, and ScienceDirect. The inclusion criteria were studies that clearly defined metaverse and cybersecurity in the digital era, were published and written in English and were peer-reviewed. Moreover, content analysis was employed. Results – The results reveal that the metaverse is a crucial future innovation of digital technology in the digital era. The metaverse adoption may multiply cybersecurity risks. Furthermore, the importance of financial cybercrime in the metaverse for authorities, corporations, and individuals to address has grown, necessitating new regulatory and compliance frameworks and novel cybersecurity mechanisms. As a result, cybersecurity is considered necessary. Conclusion – The metaverse is an essential technology with both advantages and disadvantages. The metaverse concept is expected to be central to future development and will provide significant benefits. However, its adoption may cause cybersecurity risks. Cybersecurity is essential to reduce those risks. Recommendations – The recommendation is to consider a quantitative study, such as surveys, regarding metaverse and cybersecurity in the digital era. Also, a qualitative approach, such as interviews, could give a clear view of insight results for further study. Research Implications – This review article contributed to the literature on metaverse and cybersecurity in the digital era. Therefore, it could guide future research on metaverse and cybersecurity in the digital age. It may also aid academics in broadening their research by incorporating more potential elements.